Extended difficulties following the use of psychedelic drugs: A mixed methods study - Evans, Jules; Robinson, Oliver C.; Argyri, Eirini Ketzitzidou; Suseelan, Shayam; Murphy-Beiner, Ashleigh; McAlpine, Rosalind; Luke, David; Michelle, Katrina; Prideaux, Ed (PloS one, 2023)
Long-term adverse experiences following psychedelic use can persist for weeks, months, or even years, and are relatively unexplored in psychedelic research. Our convergent mixed-method study gained quantitative and qualitative data from 608 participants who reported extended difficulties following psychedelic experiences. Data was gathered on the context of use, the nature and duration of the challenges they experienced (including a written description of these), plus a range of possible risk factors and perceived causes. The most common forms of extended difficulty were feelings of anxiety and fear, existential struggle, social disconnection, depersonalization and derealization. For approximately one-third of the participants, problems persisted for over a year, and for a sixth, they endured for more than three years. It was found that a shorter duration of difficulties was predicted by knowledge of dose, drug type and lower levels of difficulty reported during the psychoactive experience, while a narrower range of difficulties was predicted by taking the drug in a guided setting. Implications for psychedelic harm reduction are discussed.